Är ungdomars psykiska ohälsa ett uttryck för en samhällsneuros eller vantrivsel i kulturen? - Nilsson, Håkan (Socialmedicinsk tidskrift, 2024)
This article entails a close reading of Freud’s book Civilizations and Its Discontents, which was published in 1930. The purpose of this close reading is to discuss and problematize young people’s mental illness with reference to an increasing number of reports that highlight various ill-health factors among young people. In this article, these ill-health factors are interpreted as young people’s perceived dissatisfaction with contemporary culture and then acted out through escapism and succumbing to the id´s instinctive passions (drugs, bullying, criminality). A paradox that Freud brings forward in the book is the Janus-like function of society, as it contributes to conflicts of instincts and feelings of guilt, yet provides protection for suffering.